An insecticide phenotypic resistance diagnostic kit for cotton aphid Aphis gossypii Glover (Hemiptera Aphididae). Issue 12 (28th September 2022) - Huang, Weiling; Yang, Qingjie; Ji, Xuejiao; Wang, Li; Wang, Qinqin; Rui, Changhui; Cui, Li
Abstract: Background: Aphis gossypii is a notorious pest worldwide, and evidence of resistance of A. gossypii to various insecticides has been documented. Diagnostic tools for the rapid and accurate assessment of insecticide resistance are urgently needed to implement effective pest control and insecticide resistance management strategies. Results: Using this diagnostic kit based on the glass vial bioassay, detection results can be obtained in 3 h and the values of 897.86, 133.57, 12 037.45, 2849.26, 19 457.33 and 215.60 ng/cm 2 were finally identified as the actual diagnostic doses of imidacloprid, acetamiprid, thiamethoxam, nitenpyram, dinotefuran and sulfoxaflor, respectively. The regression equation between mortalities under diagnostic doses and actual resistance ratios tested by the leaf‐dipping method were conducted in different strains of A. gossypii, and the diagnostic mortality of A. gossypii was negatively correlated with the resistance ratio to imidacloprid ( r  = −0.986, P  = 0.002), acetamiprid ( r  = −0.964, P  = 0.008), thiamethoxam ( r  = −0.930, P  = 0.022), nitenpyram ( r  = −0.950, P  = 0.013), dinotefuran ( r  = −0.976, P  = 0.004) and sulfoxaflor ( r  = −0.937, P  = 0.019). Moreover, four A. gossypii field populations were selected to apply the diagnostic kit in the field. Conclusions: A diagnostic kit based on the glass vial bioassay for the rapid detection of resistance to imidacloprid, acetamiprid, thiamethoxam, nitenpyram, dinotefuran and sulfoxaflor in A. gossypii was developed. The insecticide diagnostic kit for A. gossypii can be a useful screening tool to determine effective insecticides quickly and accurately. © 2022 Society of Chemical Industry. Abstract : A diagnostic kit based on the glass vial bioassay for the rapid detection of resistance to imidacloprid, acetamiprid, thiamethoxam, nitenpyram, dinotefuran and sulfoxaflor in A. gossypii was developed. The insecticide diagnostic kit for A. gossypii can be a useful screening tool to determine effective insecticides quickly and accurately in integrated pest management programs.